Changes in cellular prion protein expression, processing and localisation during differentiation of the neuronal cell line CAD 5 - Fremuntova, Zuzana; Mosko, Tibor; Soukup, Jakub; Kucerova, Johanka; Kostelanska, Marie; Hanusova, Zdenka Backovska; Filipova, Marcela; Cervenakova, Larisa; Holada, Karel (Biology of the cell, 2020)
BACKGROUND INFORMATION: Cellular prion protein (PrPC ) is infamous for its role in prion diseases. The physiological function of PrPC remains enigmatic, but several studies point to its involvement in cell differentiation processes. To test this possibility, we monitored PrPC changes during the differentiation of prion-susceptible CAD 5 cells, and then we analysed the effect of PrPC ablation on the differentiation process. RESULTS: Neuronal CAD 5 cells differentiate within 5 days of serum withdrawal, with the majority of the cells developing long neurites. This process is accompanied by an up to sixfold increase in PrPC expression and enhanced N-terminal β-cleavage of the protein, which suggests a role for the PrPC in the differentiation process. Moreover, the majority of PrPC in differentiated cells is inside the cell, and a large proportion of the protein does not associate with membrane lipid rafts. In contrast, PrPC in proliferating cells is found mostly on the cytoplasmic membrane and is predominantly associated with lipid rafts. To determine the importance of PrPC in cell differentiation, a CAD 5 PrP-/- cell line with ablated PrPC expression was created using the CRISPR/Cas9 system. We observed no considerable difference in morphology, proliferation rate or expression of molecular markers between CAD 5 and CAD 5 PrP-/- cells during the differentiation initiated by serum withdrawal. CONCLUSIONS: PrPC characteristics, such as cell localisation, level of expression and posttranslational modifications, change during CAD 5 cell differentiation, but PrPC ablation does not change the course of the differentiation process. SIGNIFICANCE: Ablation of PrPC expression does not affect CAD 5 cell differentiation, although we observed many intriguing changes in PrPC features during the process. Our study does not support the concept that PrPC is important for neuronal cell differentiation, at least in simple in vitro conditions.
Keywords: Neurons; Cell Line; Cell Differentiation; membrane protein; posttranslational modifications; posttranslační úpravy proteinů; Mice; Protein Processing, Post-Translational; zvířata; membránové mikrodomény; Membrane Microdomains; PrPC Proteins; cell differentiation; neurony; myši; PrPC proteiny; buněčné linie; buněčná diferenciace; priony; Prions; Animals